Dinamika Regulasi Desentralisasi dan Kewenangan Pemerintah Daerah dalam Perspektif Demokratis - Bisma Pratama Harefa; Emilia Utari; Janea Arinta; Paras Yasthika B.P.A.; Reynaldi Bagastiar (CV. Multi Kreasi Media, 2022)
Decentralization has become a universal principle of governance with various forms of application in every country. This is consistent with the fact that not all government affairs can be carried out in a centralized manner, given the geographical conditions, the complexity of community development, the plurality of local social and cultural structures and demands for democratization in governance. This writing aims to describe various democratic perspectives on what is actually the goal of decentralization development. By using the normative method and analyzing several regulations regarding decentralization that have existed and are applicable in Indonesia. Article 18 of the 1945 Constitution which has been amended and added to Articles 18, 18A and 18B provides the basis for implementing decentralization. The Unitary State of the Republic of Indonesia is divided into Provinces, and the Provinces are divided into Regencies and Cities, each of which has a regional government. This constitutional mandate and consensus has long been practiced since the independence of the Republic of Indonesia with various ups and downs of goals to be achieved through decentralization. Even today, we have 7 (seven) laws governing regional government, namely: Law no. 1 of 1945; UU no. 22 of 1948; UU no. 1 of 1957; UU no. 18 of 1965; UU no. 5 of 1974; UU no. 22 of 1999; UU no. 32 of 2004; and finally Law no. 12 of 2008 concerning Regional Government. Likewise decentralization when viewed from a democratic perspective. Democracy must be seen as a continuous phenomenon. Seen from this perspective, the future of democracy is endless; elements of democracy will emerge and develop in various levels and stages at different rates in each country.